RESILIENSI KELUARGA MUSLIM DI MASA WABAH COVID-19: TINJAUAN PERAN DAN FUNGSI SUAMI ISTRI - Ranny Apriani Nusa (Sahaja: Journal Sharia and Humanities, 2022)
The Coronavirus Outbreak (COVID-19) is a crisis in the health sector that has a very significant impact on all levels of society. Economic, political, social, cultural, religious impacts and other aspects are felt by all people around the world because of this epidemic. in their distribution figures, all countries around the world make policies, advice to stay at home, do work from home, learn from home (learn from home), and so on. All of this is done so that people can avoid crowds and keep maintaining their distance (physical distance). In this study, the authors will discuss efforts to resilience (resilience) Muslim families whose research subjects are married couples. What are their roles and functions in maintaining family resilience during the Covid-19 outbreak, and so on. This research is a field research. The subject is a married couple in Bukit Mutiara Jaya Housing, Tembalang, Semarang. The investigation concluded that there are several new roles that a husband must play in family resilience, namely maintaining high-quality communication with the family, for example by holding meetings after each dinner together or in religious matters holding a new routine such as a cult after each dawn prayer, so that when he is worshiping from home, orders of morals are easy to carry out. Similar to a mother who previously served as a wife and a housewife, in the wabahc, she has increasingly become a “teacher at home” who participates and is proactive in guiding her child virtually. The functions that must be carried out by a married couple to support family resilience during the Covid-19 wabahc include the function of spirituality, the function of economic resilience, the function of communication, and the function of education.